Management of pastures - Karlsson, Karolina (2020)
Natural pastures are important for the biological biodiversity. 2004 did we have 520 000 ha of pastures in Sweden according to the Swedish agency of agriculture, today we have 461 000 ha (Jordbruksverket, 2019). By studying a survey done by the Swedish agency of agriculture 2017 and GIS-analysis of data from aerial image interpretation, I have tried to work out what’s causing farmers choice to let their animal feed in pastures. I have also analysed how intense and what type of farmlands that are grazed. The farmers that did participate in the survey preferred to let their animal feed in grown pastures rather than natural pastures, if they could choose. Analyses of the number of ” livestock unit” in relation to grown pasture and natural pasture shows that very small farms let their animals graze extensively. Animals on dairy farms are grazing intensively, and farms with sheep and beef cattle are grazing between extensively and intensively. The survey shows that the economy is important for management of pastures. But more things are affecting, like the practical work with pastures, the farmers age, lack of time and strength. Especially sheep farmers are concerned that the sheep grow less on natural pastures, they also have problems with parasites, predators and predator fences. Analyses of the aerial image interpretation shows that about 70 % of the natural pastures are grazed. Pastures and meadows in TUVA that the aerial image interpretation is overlapping are grazed by about 90 % and block pasture by about 80 %. Even in land inventoried as natural pasture you can find seminatural pastures and arable land, though natural pastures are most common. Agricultural subsidies are affecting the grazing management. The ability to apply for agricultural subsidies is affected by land leasing. Also, some of the rules for agricultural subsidies are affecting certain types of farmers, like very small farms. Most farmers that are applying for the special environment subsidies for natural pastures are satisfied with the rules and the configuration of the subsidies. Very small farms and sheepfarms are less interested to apply for this subsidy although their production is caring for the landscape. The attitude from the society and authorities towards farmers work with natural pastures is affecting the farmers commitment.